2021
DOI: 10.1186/s12870-021-03104-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tomato accessions as source of new genes for improving heat tolerance: from controlled experiments to field

Abstract: Background Due to global warming, the search for new sources for heat tolerance and the identification of genes involved in this process has become an important challenge as of today. The main objective of the current research was to verify whether the heat tolerance determined in controlled greenhouse experiments could be a good predictor of the agronomic performance in field cultivation under climatic high temperature stress. Results Tomato acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 81 publications
(124 reference statements)
2
13
0
Order By: Relevance
“…Of all the growth stages, reproductive stage is the most sensitive stage affected by negative impact of heat stress (Zinn et al, 2010). High temperature stress causes anomalies and malfunction in reproductive processes ranging from reduction in pollen germination (PGP) percentage, pollen viability percentage (PVP), malformation in ovule to inhibition in fertilization process in various crops, including rice (Xu et al, 2021), wheat (Ullah et al, 2022), chickpea (Bhandari et al, 2020;Devi et al, 2022), common bean (Silva et al, 2019;Soltani et al, 2019) and tomato (Gonzalo et al, 2021). High PGP and PVP values are indicators of efficient reproductive function leading to high pod and seed setting resulting in improved yield under heat stress (Firon et al, 2006;Pham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the growth stages, reproductive stage is the most sensitive stage affected by negative impact of heat stress (Zinn et al, 2010). High temperature stress causes anomalies and malfunction in reproductive processes ranging from reduction in pollen germination (PGP) percentage, pollen viability percentage (PVP), malformation in ovule to inhibition in fertilization process in various crops, including rice (Xu et al, 2021), wheat (Ullah et al, 2022), chickpea (Bhandari et al, 2020;Devi et al, 2022), common bean (Silva et al, 2019;Soltani et al, 2019) and tomato (Gonzalo et al, 2021). High PGP and PVP values are indicators of efficient reproductive function leading to high pod and seed setting resulting in improved yield under heat stress (Firon et al, 2006;Pham et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in controlled high temperature environment of growth chamber revealed PGP and PVP to be highly correlated with pods plant -1 and could be used as vital indicators of heat tolerance. Earlier studies have also indicated that these traits could be used for selecting heat tolerant genotypes in chickpea (Devi et al, 2022), common bean (Rainey and Griffiths, 2005), lentil (Sehgal et al, 2019) and tomato (Gonzalo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For most tomato cultivars, if the temperatures exceed 26ºC during the day and 20ºC during the night, fruit set is impaired mainly due to floral development alteration, and therefore fruit yield is reduced (Sherzod et al ., 2020). Because the response to stress varies widely between genotypes (Arena et al ., 2020; Gonzalo et al ., 2021), gaining deeper knowledge of the developmental and molecular response of various cultivars may provide clues for innovative breeding strategies aiming at improving commercial tomato cultivars for better adaptability to climate change. In the present work, we investigated the responses to heat stress in eleven tomato cultivars producing fruits of different sizes and shapes.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the post-harvest properties of these 41 accessions, such as the duration of fruit shelf life and fungal susceptibility, under normal and high temperature regimes. These genotypes have been extensively characterised for their responses to elevated temperature and/or drought growth conditions using Qualitative Trait Loci analysis, high-throughput geno-and phenotyping, assessment of flowering, fruit set, yield, fruit nutritional composition, antioxidant and anti-inflammatory activities, as well as by screening for photosynthetic efficiency [23][24][25][26][27][28][29][30][31][32][33][34]. In addition, several candidate genes regulating heat stress tolerance were recently identified in varieties from this collection [24,29].…”
Section: Selection Of Tomato Germplasm For Assessment Of Post-harvest Fruit Quality Parametersmentioning
confidence: 99%